Compressional resilience of the kapok fibrous assembly. Issue 13 (August 2014) - Yan, Jinjiang; Wang, Fumei; Xu, Bugao
Kapok fiber is light, buoyant, and excellent in thermal insulation because of its high degree of hollowness. However, it is difficult to preserve the lumen structure of kapok fiber under repetitive compression in the course of manufacturing and utilization, and then the fiber may lose its unique features quickly. Thus, it is critical to know the resilience of kapok under repeated compression and how it can be affected by environmental factors. In this paper, we studied the compressional resilience of fibrous assemblies made of slightly carded kapok fibers by using an Instron compression tester. The nonlinear compressional behavior of the assemblies was observed in the repeated transverse compressing cycles with a constant compressional strain, and three characteristic stages of the entire compressing cycles—linear elastic, metamorphosis, and densification—were identified. The plastic and the visco-elasto-plastic compressional deformations were characterized from the compressional stress–strain curve. It was found that the conditioning humidity and the number of compressing cycles could affect the compressional resilience of the kapok fibrous assembly, and that the dry-treated kapok fibrous assemblies possessed better resilience and higher strains than the wet-treated ones.